Development and Application of USB Device in Locomotive TCN - 易伟民; 肖家博 (机车电传动)
This paper analyzed the structure and the design of USB device, which was based on a coldfire CPU and the VxWorks platform. This paper introduced the multi-application of USB device in TCN. In practice, this USB device has good stability and reliability and is easy to use. The design can be applied to many types of equipment in locomotive.